Potential Azo-8-hydroxyquinoline derivatives as multi-target lead candidates for Alzheimer’s disease: An in-depth in silico study of monoamine oxidase and cholinesterase inhibitors - Fatima Zahra Guerguer; Bouchra Rossafi; Oussama Abchir; Yasir S. Raouf; Dhabya Bakhit Albalushi; Abdelouahid Samadi; Samir Chtita (PLoS ONE, 2025)
Cognitive dysfunction in Alzheimer’s disease results from a complex interplay of various pathological processes, including the dysregulation of key enzymes such as acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), and monoamine oxidase B (MAO-B). This study proposes and designs a series of novel molecules derived from 8-hydroxyquinoline (Azo-8HQ) as potential multi-target lead candidates for treating AD. An exhaustive in silico analysis was conducted, encompassing docking studies, ADMET analysis, density functional theory (DFT) studies, molecular dynamics simulations, and subsequent MM-GBSA calculations to examine the pharmacological potential of these molecules with the specific targets of interest. Out of the 63 Azo-8HQ derivatives analysed, two molecules, 14c and 17c, demonstrated strong affinities for AChE, BuChE, and MAO-B, along with favourable pharmacokinetic profiles and electronic properties. Molecular dynamics simulations confirmed the stability of these molecules within the active sites of the targets, and MM-GBSA calculations revealed low binding energies, indicating robust interactions. These findings identify molecules 14c and 17c as promising multi-target candidates for the treatment of AD, based on an in-depth computational study aimed at minimizing drug development costs and time. Future work will include the synthesis of these molecules followed by in-depth in vitro and in vivo testing to validate their potential therapeutic efficacy.